(untitled) (Swiss Medical Weekly, 2013)
OBJECTIVE: The performance of bispectral index (BIS) for the measurement of the sedative depth when dexmedetomidine is administered in propofol anaesthesia and sedation has not yet been established. This study evaluated the effects of adjunctive dexmedetomidine on the accuracy of BIS to predict loss of consciousness (LOC) and BIS values predicting LOC during propofol administration. METHODS: In this randomised, double-blind and placebo-controlled trial, 225 patients scheduled for general anaesthesia were assigned to one of three groups. Dexmedetomidine 0.5 and 1.0 µg kg–1 were intravenously infused for 15 minutes in the dexmedetomidine 0.5 and 1.0 µg kg–1groups, and saline was infused in the control group. Propofol was administered as an effect-site target-controlled infusion after completion of dexmedetomidine infusion. Patients in each group were allocated to five subgroups in which the concentration of propofol was set at 0, 1, 2, 3 and 4 μg ml–1, respectively. Three minutes after propofol administration, the BIS values and Observer’s Assessment of Alertness/Sedation (OAA/S) scores were recorded. RESULTS: There were no significant differences in the prediction probability of BIS for detecting LOC in the three groups. At the time of LOC, BIS50 values were 71.1 and 71.4 in the dexmedetomidine 0.5 and 1.0 µg kg–1groups, respectively, which were significantly larger than the BIS50 of 63.2 in the control group. CONCLUSIONS: The ability of BIS to predict LOC is not influenced by dexmedetomidine during propofol administration, but BIS values are enhanced at the time of LOC. This study has been registered with http://www.ClinicalTrials.gov (number NCT00479661)